Peran Pemerintah Nagari Sungai Pua dalam Upaya Penanggulangan Banjir Lahar Dingin Pasca Erupsi Gunung Marapi - Ahmad Radifan. S; Yuliarti (Al-DYAS, 2026)
Cold lahar flooding following the eruption of Mount Marapi has caused significant damage to settlements, agricultural land, infrastructure, and the socioeconomic activities of communities in Agam Regency. This condition requires the active role of the nagari government as the frontline level of government in implementing disaster management and recovering affected areas. This study aimed to analyze the role of the Sungai Pua Nagari Government in managing cold lahar flooding following the eruption of Mount Marapi and to identify the supporting and inhibiting factors affecting its implementation. The study employed a qualitative approach with a descriptive design. Informants were selected purposively and comprised representatives of the Nagari Government, relevant agencies, and affected communities. Data were collected through observation, interviews, and documentation and were subsequently analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results showed that the Sungai Pua Nagari Government performed its role through three aspects, namely as a regulator, facilitator, and implementer. As a regulator, the nagari government formulated policies and supported the management of disaster-prone areas. As a facilitator, the nagari government coordinated various parties and facilitated the distribution of assistance, the relocation of residents, the recovery of agricultural land, and infrastructure repairs. As an implementer, the nagari government was directly involved in rehabilitation, reconstruction, and community mutual-assistance activities. The implementation of these roles was supported by high community participation, interinstitutional coordination, and support from the government and volunteers. However, limited budgets, human resources, facilities and infrastructure, and the extensive affected area meant that the recovery process had not yet been fully optimized. This study concluded that the Sungai Pua Nagari Government had performed a strategic role in post-disaster management and recovery, but the effectiveness of its implementation still required stronger institutional and resource capacity. These findings provide practical implications for nagari governments in improving coordination, resource preparedness, and the sustainability of disaster management programs in disaster-prone areas.